Apelin‐13/APJ induces cardiomyocyte hypertrophy by activating the Pannexin‐1/P2X7 axis and FAM134B‐dependent reticulophagy. Issue 4 (6th February 2022) - Yang, Yiyuan; Zhang, Kai; Huang, Shifang; Chen, Wei; Mao, Hui; Ouyang, Xueqian; Chen, Linxi; Li, Lanfang
Abstract: Cardiac hypertrophy is a leading cause of cardiac morbidity and mortality worldwide. Apelin is the endogenous ligand for the G protein‐coupled receptor, APJ. Previously, we have revealed that apelin‐13 can induce cardiomyocyte hypertrophy by activating the autophagy pathway. However, the precise mechanism through which apelin‐13 regulates reticulophagy to participate in cardiomyocyte hypertrophy remains unclear. Herein, we observed that apelin‐13‐induced cardiomyocyte hypertrophy by activating FAM134B‐dependent reticulophagy via the Pannexin‐1/P2X7 signal pathway. Furthermore, we found that apelin‐13 stimulated the opening of Pannexin‐1 hemichannel and increased extracellular ATP (eATP) levels, which activated the P2X7 purinergic receptor. Activation of the Pannexin‐1/eATP/P2X7 axis subsequently led to FAM134B‐dependent reticulophagy. Moreover, inhibition of the Pannexin‐1/P2X7 axis and FAM134B‐dependent reticulophagy reversed apelin‐13‐induced cardiomyocyte hypertrophy. Based on our present findings, apelin‐13/APJ induces cardiomyocyte hypertrophy by activating the Pannexin‐1/P2X7 axis and FAM134B‐dependent reticulophagy. Abstract : (1) Apelin‐13 promoted selective reticulophagy in cardiomyocytes. (2) Apelin‐13 triggered the occurrence of FAM134B‐dependent reticulophagy via activation of Pannexin‐1/P2X7 axis in cardiomyocytes. (3) FAM134B‐dependent reticulophagy pathway activation mediated apelin‐13‐induced cardiomyocyte hypertrophy. (4) Inhibition of Pannexin‐1/P2X7 axis and the FAM134B‐dependent reticulophagy would be a potential strategy for cardiomyocyte hypertrophy therapy.